2010
DOI: 10.1080/14786410802394132
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from the leaves ofMichelia alba

Abstract: (-)-N-Formylanonaine (1), (-)-oliveroline (2), (+)-nornuciferine (3), lysicamine (4), (+)-cyperone (5), (+)-epi-yangambin (6), ficaprenol-10 (7), pheophytin a (8), aristophyll C (9) and michephyll A (10) were isolated from the leaves of Michelia alba DC (Magnoliaceae). Among them, 10 is a new compound. The structures of these compounds were characterised and identified by spectral analyses. We have also presented the antioxidation activity of 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The ferrous ion-chelating potential of chlorophyll was investigated according to a method described previously (Decker and Welch, 1990;Wang et al, 2010). Briefly, various testing concentrations of samples dissolved in DMSO were added to a solution of 2 mM FeCl 2 Á4H 2 O (0.05 ml).…”
Section: Metal Chelating Activitymentioning
confidence: 99%
“…The ferrous ion-chelating potential of chlorophyll was investigated according to a method described previously (Decker and Welch, 1990;Wang et al, 2010). Briefly, various testing concentrations of samples dissolved in DMSO were added to a solution of 2 mM FeCl 2 Á4H 2 O (0.05 ml).…”
Section: Metal Chelating Activitymentioning
confidence: 99%
“…Rice grass contains chlorophyll as a major ingredient and pheophytin (or pheo) as the second most abundant component ( Figure 11). Pheophytin is synthesized in rice grass, spinach (Spinacia oleracea) leaves and Michelia alba leaves, but is not a degradation product of chlorophyll [159], and the compound reveals a level of antioxidant activity that is similar to that of ubiquinone [160].…”
Section: Mango (Mangifera Indica L)mentioning
confidence: 99%
“…The reducing power of (−)-N-formylanonaine (100 µM) was reported at 0.56, a moderate value compared with 1.28 for 3-tert-butyl-4-hydroxyanisole (BHA), a standard antioxidant [ 21 ]. In addition, Wang et al [ 21 ] reported the isolation of several bioactive compounds including michephyll A from the leaves of M. alba [ 78 ]. Analysis of the antioxidant activity of michephyll A (100 µM) using ABTS free radical scavenging and metal chelating activities showed moderate antioxidant activity with 40.5 and 55.2% inhibitions, respectively [ 78 ].…”
Section: Therapeutic Potential Of M Alba Metabolitesmentioning
confidence: 99%
“…In addition, Wang et al [ 21 ] reported the isolation of several bioactive compounds including michephyll A from the leaves of M. alba [ 78 ]. Analysis of the antioxidant activity of michephyll A (100 µM) using ABTS free radical scavenging and metal chelating activities showed moderate antioxidant activity with 40.5 and 55.2% inhibitions, respectively [ 78 ].…”
Section: Therapeutic Potential Of M Alba Metabolitesmentioning
confidence: 99%